2021
DOI: 10.1038/s41598-021-91900-1
|View full text |Cite
|
Sign up to set email alerts
|

Selective stimulation of the ferret abdominal vagus nerve with multi-contact nerve cuff electrodes

Abstract: Dysfunction and diseases of the gastrointestinal (GI) tract are a major driver of medical care. The vagus nerve innervates and controls multiple organs of the GI tract and vagus nerve stimulation (VNS) could provide a means for affecting GI function and treating disease. However, the vagus nerve also innervates many other organs throughout the body, and off-target effects of VNS could cause major side effects such as changes in blood pressure. In this study, we aimed to achieve selective stimulation of populat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Recent studies of VNS suggest that smaller, multi-contact electrodes may provide better selectivity for isolating desired therapeutic effects from off-target side effects (Fitchett et al, 2021; Ordelman et al, 2013; Shulgach et al, 2021). Specifically, the studies demonstrated that the magnitude of heart rate changes may be altered by changing the electrode location around the circumference of the VN.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of VNS suggest that smaller, multi-contact electrodes may provide better selectivity for isolating desired therapeutic effects from off-target side effects (Fitchett et al, 2021; Ordelman et al, 2013; Shulgach et al, 2021). Specifically, the studies demonstrated that the magnitude of heart rate changes may be altered by changing the electrode location around the circumference of the VN.…”
Section: Introductionmentioning
confidence: 99%
“…As in our prior experiments ( Patel et al, 2018 ; Bielanin et al, 2020 ; Miller et al, 2020 ), animals were gradually acclimated over at least 5 weeks for 1-h of confinement in a nylon restraint bag attached to a recording platform using Velcro straps. Subsequently, an aseptic recovery surgery was performed in a dedicated operating suite as described below to attach two-contact platinum-iridium 90/10 electrodes in a silicone patch (Micro-leads Inc, Somerville, MA, United States), similar to those used in prior studies ( Nanivadekar et al, 2019 ; Shulgach et al, 2021 ), to the proximal duodenum and gastric antrum, on the ventral surface ( Figure 1 ). In addition, custom-fabricated electrodes consisting of flexible insulated wire (Cooner Wire, Chatsworth, CA United States) embedded in medical grade silicon (Bentec Medical, Woodland, CA United States) were attached to the diaphragm and abdominal muscles ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The acute action of this agent allowed us to monitor a variety of physiologic parameters prior to emesis during a controlled recording session. Before and following CuSO 4 treatment we recorded heart rate, respiration rate, and gastric and duodenal myoelectric responses using methodology developed through our work in ferrets ( Nanivadekar et al, 2019 ; Shulgach et al, 2021 ). The dose of CuSO 4 was additionally varied between animals so we could determine whether increasing the dose altered physiologic responses prior to emesis.…”
Section: Introductionmentioning
confidence: 99%
“…As in our prior experiments (Patel et al, 2018; Bielanin et al, 2020; Miller et al, 2020), animals were gradually acclimated over at least 5 weeks for 1-hour of confinement in a nylon restraint bag attached to a recording platform using Velcro straps. Subsequently, an aseptic recovery surgery was performed in a dedicated operating suite as described below to attach two-contact platinum-iridium 90/10 electrodes in a silicone patch (Micro-leads Inc., Somerville, MA, USA), similar to those used in prior studies (Nanivadekar et al, 2019; Shulgach et al, 2021), to the proximal duodenum and gastric antrum, on the ventral surface ( Figure 1 ). In addition, custom-fabricated electrodes consisting of flexible insulated wire (Cooner Wire, Chatsworth, CA USA) embedded in medical grade silicon (Bentec Medical, Woodland, CA USA) were attached to the diaphragm and abdominal muscles ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%